Constructed Wetland for wastewater treatment: a case study at Frangipani Resort, Langkawi - Mohd Shafiq Asnawi Md. Akhir,; Ahmad Aldrie Amir,; Mazlin Mokhtar,; Wong, Anthony Kim Hooi (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Wetland is a shallow watery area that has slow movement or static hydrology. It usually consists of floating and submerged plants with high level of biodiversity and plays a role in treating water of lakes and rivers. Constructed wetland, on the other hand is a man-made system that imitates the natural wetland in the aspects of structure and function. Some facilities like hotels, resorts and housing areas have taken initiatives to manipulate this ability and build their own constructed wetlands to treat sewage water. For facilities like hotels, a sewage treatment system with low technology, low energy requirements, affordable and easy to maintain is a crucial need. Therefore, it is proposed that constructed wetland is an efficient solution. Frangipani Resort & Spa in Langkawi Geopark is one of the hotels in Malaysia that advanced this eco-technology into their facility since 2009. By having this, enormous benefits are gained especially in the investment of hotel’s financial capital in cutting cost of sewage maintenance and water usage. Plus, the system itself would indirectly help to ensure more sustainable wastewater and water resource management when the treated wastewater is reused. Although there are a lot of studies on constructed wetlands that are used to treat wastewaters from municipal, industrial and agricultural areas, there is insufficient study that link constructed wetland and wastewaters from lodging industry. Therefore, this proposed study will focus on (i) how efficient a decent and functional constructed wetland built within a resort can help reduce the maintenance cost, energy usage and pollution from untreated wastewater; and (ii) how significant can the system be to create a resort with sustainable wastewater management which ultimately can be replicated in an urban setting to reduce the stress of wastewater treatment.